Prediksi Biaya Pemakaian Listrik Dengan Metode Logika Fuzzy Mamdani - Zalmi, Wahyuni Fithratul; Pang, David; Nurgraha, Mahendra Kusuma (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Understanding the electricity tariff class is needed to predict how much usage costs or electricity bills that must be incurred by customers. Each power capacity has a different basic electricity tariff based on the class, household, business and industry. Fuzzy logic can solve problems with imprecise and heuristic data by producing accurate conclusions. The conclusion obtained from the Fuzzy Logic results is expected to be a consideration for customers in predicting electricity usage costs based on electricity tariff groups and customer electrical power capacity. The proposed research uses the Mamdani Fuzzy Logic Method, the use of this method aims to facilitate customers in predicting the cost of electricity usage based on the electricity tariff class and the customer's electric power capacity. The output of this research is the result of predicting the cost of electricity usage based on the power group in residential homes. The higher the tariff group, the number of kWh, electronic goods, and usage time, the higher the predicted energy consumption used. The results obtained from adjusting the fuzzy input antecedents and fuzzy values, namely [900;850;30;20], then for Type_Tariff Power 900, Total_KWh 850, Electronics 30, and Time_Use 20 is 986. Then the cost that must be incurred in the example case above is 1,333,072 rupiah.